2000
DOI: 10.1103/physrevlett.84.2199
|View full text |Cite
|
Sign up to set email alerts
|

Generic Dynamic Scaling in Kinetic Roughening

Abstract: We study the dynamic scaling hypothesis in invariant surface growth. We show that the existence of power-law scaling of the correlation functions (scale invariance) does not determine a unique dynamic scaling form of the correlation functions, which leads to the different anomalous forms of scaling recently observed in growth models. We derive all the existing forms of anomalous dynamic scaling from a new generic scaling ansatz. The different scaling forms are subclasses of this generic scaling ansatz associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
251
4
27

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 230 publications
(300 citation statements)
references
References 19 publications
12
251
4
27
Order By: Relevance
“…In addition, these studies suggest superroughening of the interface, with ζ > 1 at depinning [169], although with nonetheless apparently mono-affine scaling. Experimentally, such anomalous scaling, previously reported in fracture surfaces [170,171], has also been extracted for ferromagnetic domain walls in ultrathin films [172]. Investiga- • C. The vertical (magenta) bar corresponds to 7 µm.…”
Section: Towards More Complex Physics At Domain Wallsmentioning
confidence: 96%
“…In addition, these studies suggest superroughening of the interface, with ζ > 1 at depinning [169], although with nonetheless apparently mono-affine scaling. Experimentally, such anomalous scaling, previously reported in fracture surfaces [170,171], has also been extracted for ferromagnetic domain walls in ultrathin films [172]. Investiga- • C. The vertical (magenta) bar corresponds to 7 µm.…”
Section: Towards More Complex Physics At Domain Wallsmentioning
confidence: 96%
“…These fluctuations can be characterized by means of different functions: power spectrum, S(q, t), global width function W (L, t), height-height correlation function, G(l, t) and local width function, w(l, t), where L is the system size and l is a local length. From these functions behavior we can obtain a set of critical exponents: global, local and spectral roughness exponents, α, α l and α s , respectively, growth exponent, β, and dynamical exponent, z [10]. A scaling law links α, β, and z as, z = α/β.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has recently been shown that the existence of power-law scaling of the correlation functions (i.e. scale invariance) does not determine a unique dynamic scaling form of the correlation functions [24]. On the one hand, there are super-rough processes, α > 1, for which α loc = 1 always.…”
mentioning
confidence: 99%
“…On the one hand, there are super-rough processes, α > 1, for which α loc = 1 always. On the other hand, there are intrinsically anomalous roughened surfaces, for which the local roughness α loc < 1 is actually an independent exponent and α may take values larger or smaller than one depending on the universality class (see [4,24] and references therein). The existence of intrinsically anomalous roughened surfaces is a most intriguing observation and leads to the still open question concerning the basic physical features (symmetries, form of the nonlinearities, conservation laws, non-locality, etc) required for anomalous roughening to occur in surface growth.…”
mentioning
confidence: 99%